Doctoral supervision as an academic practice and leader–member relationship: A critical approach to relationship dynamics - Vähämäki Maija; Saru Essi; Palmunen Lauri-Matti (Elsevier, 2022)
Recent rationalisation of academic work has challenged the role of traditional supervision, which
still plays a significant part in students’ experiences of their doctoral studies. Accordingly, we give
a voice to doctoral students’ lived experiences and trace how relationship dynamics are constructed
during encounters between the supervisor and supervisee in the contemporary academic
context. We approach the topic with interview data and written stories from 33 doctoral students.
First, aided by the LMX theory, our findings demonstrate supervisory relationships to be leader–
follower relationships that contain imbalanced power relations. Second, a narrative reading of
our data helped us identify the critical moments and encounters that pushed relationships towards
either a fruitful co-operation or a destructive endeavour. Our findings add a critical view to
the mainstream pedagogical research on supervising practices. In addition, we contribute to the
research on doctoral students’ wellbeing by demonstrating how a combination of intertwined
elements explain the overall satisfaction and experience of the supervision.